Conceptual & Legal Framework of Islamic Finance - Aliqoriev O.F. (Web of Journals Publishing, 2023)
This article discusses the theoretical and legal foundations of Islamic finance, analyzes the current state of the global Islamic finance industry. Scientific conclusions on Islamic economics and Islamic finance and its components are given.
Keywords: Shariah principles, Islamic Economy, Islamic finance, Islamic banking, Financial Intermediation, Islamic Finance Market.